The Study of Teaching Speaking by Retelling Story - Ridwan Ridwan; Nurul Hasanah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
By speaking, everyone can express what they think or feel. Therefore, speaking is one of the most important competencies that students must master at school, while tenth grade students still had problems in speaking. Most of them were difficult to explore ideas and designing their sentences. Besides they were also less vocabulary. This Aim of research is to describe the study of teaching speaking by retelling story at Tenth grade students of SMA Favorit NU Tegaldlimo in the academic year 2019/2020. This research is a qualitative descriptive research. The study subject of grade X science students of SMA Favorit NU Tegaldlimo. This research involved nineteen students at the tenth grade students of science in SMA Favorit NU Tegaldlimo as population. There were twelve female students and seven male students. In addition, the researcher used a qualitative as approach, there were data collection techniques used to collect data such as the interview, observation, and documentation. There were several aspects of speaking that student's increased in retelling story of narrative texts such as (Orientation, complication, resolution). Furthermore, Students were also more enthusiastic and enjoy being taught by retelling narrative story. According to described data, it showed that there was improvement of students’ scores in speaking narrative text from the preliminary study test until after study. Finally, students got an improvement, 100 % of students passed from SKM. from these results the researchers concluded that teaching speaking by retelling story was been successful in increasing students' abilities in speaking skill.